Analysis of the performance of Khartoum Customs Department during the period 2019-2021 - Mohammed, Akram AbdEldaim (Journal of Economic, Administrative and Legal Sciences, 2023)
The aim of this study was to investigate the performance of the Khartoum Customs Department. The problem of the study was to determine the contribution of the customs stations that make up the Khartoum Customs Department. The study claimed that the dry port of Soba had the greatest impact on the performance of the Khartoum Customs Department. To achieve the objective of the study, monthly data for the Khartoum Customs Department was collected from 2019 to 2021. The study concluded that the largest customs revenues achieved in the Khartoum Customs Department were from the Soba dry port (971.9206), while the lowest revenues were from the warehouses management (150.8236). Additionally, all customs stations in the Khartoum Customs Department showed an increase in performance in 2019, and all customs stations in the Khartoum Customs Department saw an increase in performance in the fourth quarter of each year during the study period.
Keywords: Customs; SUBA dry port; Sudan Customs